Garimpeiros de Ouro e Cooperativismo no século XXI. Exemplos nos rios Tapajós, Juma e Madeira no Sudoeste da Amazônia Brasileira - Maria Célia Coelho; Luiz Jardim Wanderley; Reinaldo Costa (Confins)
This article discusses: 1) who are the small scale miners in the contemporary Brazilian Amazon, how they act and what are their characteristics in comparison with other forms of mining; and 2) the informality of small scale mining in opposition to the idea of "modernization" through industrial mining, hydroelectric or agribusiness and also through the recent environmental legislation and the strengthening of mining cooperative organizations. Based mainly on fieldwork and economic regulation and spatial restructuring theories, we analyze how the "modernization" process triggered by industrial mining, hydroelectric and agribusiness affects the artisanal small miner in the southwest of the Brazilian Amazon, especially due to the hardening of the environmental and the mineral resources controls. We conclude in this study that there is a complex diversity of gold mining, ranging from small artisanal, informal and descapitalize gold miners; passing through percentistas, workers paid in percentages of the extraction; miners who are owners of mines, balsas and dredgers or who are investors; family or capitalized miners cooperatives; and mining corporations. In the current Amazonian context, "modern" and capital-intensive projects, with strong state support, have been pressing small-scale miners, making their work unfeasible. To those, the ways to maintain their livehood are: to associate into family cooperatives or to form unequal alliance with capitalized miners and with mining corporations.